Reading Logs and Literature Teaching Models in English Language Teacher Education - Ornella Ochoa Delarriva; Enrique Alejandro Basabe (Asociación Colombiana de Profesores de Ingles, 2015)
Reading logs are regularly used in foreign language education since they are not only critical in the development of reading comprehension but may also be instrumental in taking readers beyond the referential into the representational realms of language. In this paper we offer the results of a qualitative analysis of a series of reading logs written by advanced students for a literature course in an English language teacher education program in Argentina. The logs were coded according to the different literature teaching models followed in the program, which let us ponder on the applicability and usefulness of reading logs, and on the need to promote diversity in literature teaching in English language teacher education.